2015
DOI: 10.1371/journal.pgen.1005003
|View full text |Cite
|
Sign up to set email alerts
|

The Bicoid Class Homeodomain Factors ceh-36/OTX and unc-30/PITX Cooperate in C. elegans Embryonic Progenitor Cells to Regulate Robust Development

Abstract: While many transcriptional regulators of pluripotent and terminally differentiated states have been identified, regulation of intermediate progenitor states is less well understood. Previous high throughput cellular resolution expression studies identified dozens of transcription factors with lineage-specific expression patterns in C. elegans embryos that could regulate progenitor identity. In this study we identified a broad embryonic role for the C. elegans OTX transcription factor ceh-36, which was previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 74 publications
(97 reference statements)
2
50
0
Order By: Relevance
“…Moreover, conditional mutants generated via CRISPR-Cas9 gene editing induced in ciliated neurons (Shen et al, 2014) exhibited AWB defects (Figure S2). Finally, AWB defects in grdn-1(ns303) animals were significantly rescued upon expression of grdn-1 under the ceh-37 promoter (Figure 2F) that drives expression transiently, but not exclusively, in the AWB neurons shortly after their birth (Lanjuin et al, 2003; Walton et al, 2015). These results suggest but do not confirm that grdn-1 acts cell-autonomously during early embryogenesis to regulate AWB morphology.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, conditional mutants generated via CRISPR-Cas9 gene editing induced in ciliated neurons (Shen et al, 2014) exhibited AWB defects (Figure S2). Finally, AWB defects in grdn-1(ns303) animals were significantly rescued upon expression of grdn-1 under the ceh-37 promoter (Figure 2F) that drives expression transiently, but not exclusively, in the AWB neurons shortly after their birth (Lanjuin et al, 2003; Walton et al, 2015). These results suggest but do not confirm that grdn-1 acts cell-autonomously during early embryogenesis to regulate AWB morphology.…”
Section: Resultsmentioning
confidence: 98%
“…It is only when the parallel regulators unc‐120/SRF and hnd‐1/HAND are removed as well that muscle differentiation is completely lost (Fukushige et al ., ). Similarly, in unc‐30;ceh‐36 double mutants, we observed partially penetrant defects in cell division and position as well as expression of the downstream lineage‐specific TF mls‐2/Hmx (Walton et al ., ). This suggests that even essential TFs or TF combinations may have additional redundant partners in any given cellular differentiation decision, thus lethality in mutant animals is a function of the number and identity of cells impacted along with the penetrance of the individual defects.…”
Section: Lineally Repetitive Transcription Factors Act Redundantly Tomentioning
confidence: 98%
“…Indeed several examples of non‐paralogous parallelism have been identified. We showed that the homeodomain TFs ceh‐36/Otx and unc‐30/Pitx are redundantly required for robust specification of two early embryonic lineages (Walton et al ., ). These TFs are coexpressed early in the ABplp and ABprp lineages and have distinct expression in other lineages.…”
Section: Lineally Repetitive Transcription Factors Act Redundantly Tomentioning
confidence: 99%
“…The endoderm GRN is therefore robust to genetic variation because many genes make both overlapping and additive contributions to gut specification. Redundancy of this type has been seen in other lineages in the C. elegans embryo, suggesting it is a general strategy for network robustness in cell‐specification GRNs (Good et al, ; Baugh et al, ; Fukushige et al, ; Broitman‐Maduro et al, ; Walton et al, ).…”
Section: The Endoderm Gene Regulatory Networkmentioning
confidence: 99%